Rancang Bangun Sistem Informasi Simpanan pada BMT Istiqomah Syariah Kutoarjo - Damar Eko Cahyono (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2026)
Islamic Microfinance Institutions (BMT) play a strategic role in community economic empowerment; however, their operational efficiency is often hindered by manual data management systems. BMT Istiqomah Syariah Kutoarjo faces challenges such as risks of recording errors in savings transactions, data duplication, and delays in preparing monthly financial reports. This study aims to design and develop an integrated savings information system to enhance accuracy and operational efficiency. The system development methodology employed is the Waterfall model, encompassing requirement analysis, system design, coding, and testing phases. The results indicate that the developed information system is capable of automating the entire cycle of member savings transactions and generating financial reports in real-time. The implementation of this system is proven to minimize potential human errors and increase service transparency for members. This system is expected to serve as a digital foundation for BMT Istiqomah Syariah Kutoarjo in improving service quality and management accountability.